The assessment of light sources - Paul, Brendon Mark (Department of Electrical Engineering, 2016)
Discomfort glare from normal sources has been thoroughly researched over the last five decades and agreement has been reached by the CIE to express it by the Unified Glare Rating (UGR) formula: UGR = 8 log₁₀g where: g = (0.785/Eᵢ)Σ(L²ω/p²) (see Glossary) Hardly any research, however, has been done on discomfort glare from small sources, so the definition of a small source was just not known. It was not known whether to define it as an effective solid angle, ros or area, As. Two hypotheses were put forward concerning the effective size of a small source: Hypothesis # 1 ('constant omega' hypothesis) The effective size of a small source has a solid angle, ros. Any source with an actual solid angle less than ros shall be considered a small source and will have an effective solid angle equivalent to ros when viewed off the line of sight (LoS). This solid angle, ros is a constant. i.e. it remains the same irrespective of distance from the source. Hypothesis # 2 ('constant area' hypothesis) The effective size of a small source has an area, As. Any source with a projected area less than As shall be considered a small source and will have an effective area equivalent to As when viewed off the line of sight (LoS). This area, As is a constant. i.e. its solid angle varies inversely proportional to the square of the distance from the source.